Coaching, Mentoring, Leadership Transformation and Employee Engagement: A Review of the Literature - Primadi Candra Susanto; Ni Nyoman Sawitri (Dinasti Publisher, 2022)
Employee engagement has been widely discussed in the study of human resource management in an effort to reduce turnover rates in a company. This article aims to review and synthesize a review of related literature on coaching, mentoring, transformational leadership, employee engagement and to see the results of research on these variables. variables to be reviewed and whether there is influence between one variable and another. This study uses a literature review by looking for references related to the variables of 20 international articles. This study provides an overview of the articles obtained by describing the influence between variables. The results of the study show that several variables have an influence on the evidence of exposure in a matrix. The employee engagement study in this literature review article explicitly focuses on supporting variables that can increase employee engagement, namely coaching, mentoring, transformational leadership.